A person‐centred, theory‐based, behavioural intervention programme for improved oral hygiene in adolescents: A randomized clinical field study. (23rd February 2022) - Dimenäs, Sandra L.; Jönsson, Birgitta; Andersson, Jessica S.; Lundgren, Jesper; Petzold, Max; Abrahamsson, Ingemar; Abrahamsson, Kajsa H.
Abstract: Aim: To test the effectiveness of a person‐centred and theory‐based educational intervention to increase adolescents′ adherence to adequate oral hygiene behaviour, that is, self‐performed periodontal infection control. Materials and Methods: Data were derived from a prospective, multi‐centred, two‐arm, quasi‐randomized field study in which treatment was performed by dental hygienists (DHs) within the Public Dental Service, Västra Götaland, Sweden. Adolescents with poor oral hygiene conditions were invited to participate. The test intervention was based on cognitive behavioural theory and principles, and the DHs used a collaborative communicative approach, inspired by motivational interviewing. The control intervention consisted of conventional information/instruction. Clinical assessments and oral hygiene behaviours were evaluated at 6 months. Results: Three‐hundred and twelve adolescents were enrolled, of whom 274 followed the treatment to 6‐month follow‐up. There were significant improvements in gingival bleeding and plaque scores for both treatment groups at 6 months, with significantly greater improvements in the test group. Adolescents in the test group brushed their teeth and used interdental cleaning aids more frequently compared to participants in the control group at 6 months. Conclusion: A person‐centred and theory‐based oral health education programme is more effective than conventional oral health education in improving adolescents' oral hygiene behaviour and periodontal infection control. ClinicalTrials.gov (NCT02906098).